PENGARUH KARAKTERISTIK GAYA BELAJAR GENERASI Z DAN MOTIVASI BELAJAR TERHADAP PRESTASI AKADEMIK MAHASISWA PRODI PENDIDIKAN ADMINISTRASI PERKANTORAN ANGKATAN 2023 UNIVERSITAS NEGERI MEDAN - Cintia Sejahtraria Nadeak; Ellys Siregar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the influence of Generation Z learning style characteristics and learning motivation on the academic achievement of students in the Office Administration Education Study Program, Class of 2023, Medan State University. The research employed an ex post facto design with a quantitative approach. The population consisted of 71 students, all of whom were taken as the sample using a saturated sampling technique. Data were collected through observation, documentation, and questionnaires, which were first tested for validity using the Product Moment correlation and reliability using Cronbach’s Alpha. Data were analyzed using multiple linear regression with the aid of SPSS version 26. The results showed that Generation Z learning style characteristics had a positive and significant effect on student’s academic achievement, with a t-value of 5.882 > t-table 1.997 and a significance level of 0.000 < 0.05. Likewise, learning motivation had a positive and significant effect, with a t-value of 4.267 > t-table 1.997 and a significance level of 0.000 < 0.05. Furthermore, the coefficient of determination (R²) was 0.683 or 68.3%. These findings confirm that Generation Z learning style characteristics and learning motivation have a significant positive influence on the academic achievement of Office Administration Education students, Class of 2023, Faculty of Economics, Medan State University.